The Effects of Injury Preventive Warm-Up Programs on Knee Strength Ratio in Young Male Professional Soccer Players - Daneshjoo, A.; Mokhtar, A.H.; Rahnama, N.; Yusof, A. (Public Library of Science, 2012)
Purpose We aimed to investigate the effect of FIFA 11+ (11+) and HarmoKnee injury preventive warm-up programs on conventional strength ratio (CSR), dynamic control ratio (DCR) and fast/slow speed ratio (FSR) in young male professional soccer players. These ratios are related to the risk of injury to the knee in soccer players.